Towards an Inclusive India with eAccessibility (International Journal of Engineering and Computer Science, 2018)
Accessibility is a measure of the extent to which a product or service can be used by a person with a disability as effectively as it can be used by a person without that disability.” If a blind person can use all the functions of an ATM machine just as easily as a sighted person, then that machine can be said to be fully accessible to blind people. However, a person in a wheelchair might find the same ATM machine difficult or impossible to use. It would then be described as “inaccessible to a person in a wheelchair”.